CULTIVATING MODERATION: AN EXAMINATION OF LOLO TAU IN THE TALLU LOLONA PHILOSOPHY FOR RELIGIOUS MODERATION EDUCATION IN THE TORAJA COMMUNITY - Welem, Theofilus (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The presence of many beliefs and practices in society necessitates the inclusion of moderation education as a crucial component in individuals' lives, with one approach being the incorporation of local knowledge. This is crucial for fostering social cohesion. This dissertation examines and presents an overview of a specific aspect of the Tallu Lolona philosophy, specifically Lolo Tau, as a means of imparting religious moderation instruction in the lives of the diverse Toraja community. The research methodology employed is descriptive qualitative, namely in the form of a literature review. The findings indicated that the significance of Lolo Tau in the Tallu Lolona philosophy represents a cultural value derived from indigenous knowledge, which may serve as a foundation for imparting religious moderation instruction. The reason for Lolo Tau's reflection of lofty human qualities, such as compassion, honesty, and generosity, is derived from his own character, as well as from other individuals, ancestors, spirits, and the surrounding natural environment. The duty to preserve concord with other people is indissoluble from a duty to the Creator. The findings of this study suggest that religious moderation education should not just rely on interfaith dialogue or religious organizations, but may also be enhanced by including the positive qualities found in local wisdom.Pluritas dalam kehidupan sosial keagamaan memerlukan pendidikan moderasi sebagai sebuah bagian penting untuk ditanamkan dalam kehidupan masyarakat, salah satunya melalui kearifan lokal. Hal ini penting sebagai bagian untuk menciptakan harmonisasi sosial. Tulisan ini menganalisis serta memberikan gambaran mengenai salah satu bagian dari falsafah Tallu Lolona yaitu Lolo Tau sebagai sumber pendidikan moderasi beragama dalam kehidupan masyarakat Toraja yang plural. Metode penelitian yang digunakan adalah kualitatif deskriptif berupa studi Pustaka. Hasil penelitian menujukkan bahwa nilai Lolo Tau dalam falsafah Tallu Lolona merupakan suatu nilai budaya kearifan lokal yang dapat digunakan sebagai sumber pendidikan moderasi beragama. Hal ini karena Lolo Tau merefleksikan nilai-nilai kemanusiaan yang tinggi, yaitu kebaikan, keikhlasan, dan kemurahan hati yang berasal dari dirinya, sesame manusia, nenek moyang, roh-roh dan alam di sekitarnya. Kewajiban menjaga keharmonisan dengan sesama manusia ini tidak terlepas dari sebuah tanggungjawab terhadap Sang Pencipta. Berdasarkan hasil penelitian ini, harapannya pendidikan moderasi beragama tidak hanya dilakukan melalui dialog antar agama ataupun melalui insitusi keagamaan, namun juga dapat diperkuatkan dengan menggunakan nilai-nilai kebaikan yang ada dalam kearifan lokal.